Cave Archaeology in Turkey - Yamaç, Ali; Gilli, Eric; Tok, Ezgi; Törk, Koray (Springer International Publishing, 2021)
We have comprehensive reports on archaeological surveys and excavations conducted in a total of about 90 caves in Turkey. There were several more studies conducted in the 1940s, but the publications of these researches are uninformative. Even though there are archaeological excavations conducted in a limited number of caves during the recent years, the results are striking. Numerous tools dating back to tens of thousands, even hundreds of thousands of years were found and important archaeological explorations were made in not just the important excavations conducted in long periods that were explained in Chap. 5, but also in excavations of smaller scales. Interestingly, no hominid or Neanderthal skeletal remains were found in almost none of the aforementioned excavations, except a few small pieces. These smaller-scale cave excavations that have given various kinds of findings are explained in this chapter.